A new perspective on drug-resistant epilepsy in children with focal cortical dysplasia type 1: From challenge to favorable outcome - Splitkova, Barbora; Mackova, Katerina; Koblizek, Miroslav; Holubova, Zuzana; Kyncl, Martin; Bukacova, Katerina; Maulisova, Alice; Straka, Barbora; Kudr, Martin; Ebel, Matyas; Jahodova, Alena; Belohlavkova, Anezka; et al. (Epilepsia, 2025)
OBJECTIVE: We comprehensively characterized a large pediatric cohort with focal cortical dysplasia (FCD) type 1 to expand the phenotypic spectrum and to identify predictors of postsurgical outcomes. METHODS: We included pediatric patients with histopathological diagnosis of isolated FCD type 1 and at least 1 year of postsurgical follow-up. We systematically reanalyzed clinical, electrophysiological, and radiological features. The results of this reanalysis served as independent variables for subsequent statistical analyses of outcome predictors. RESULTS: All children (N = 31) had drug-resistant epilepsy with varying impacts on neurodevelopment and cognition (presurgical intelligence quotient [IQ]/developmental quotient scores = 32-106). Low presurgical IQ was associated with abnormal slow background electroencephalographic (EEG) activity and disrupted sleep architecture. Scalp EEG showed predominantly multiregional and often bilateral epileptiform activity. Advanced epilepsy magnetic resonance imaging (MRI) protocols identified FCD-specific features in 74.2% of patients (23/31), 17 of whom were initially evaluated as MRI-negative. In six of eight MRI-negative cases, fluorodeoxyglucose-positron emission tomography (PET) and subtraction ictal single photon emission computed tomography coregistered to MRI helped localize the dysplastic cortex. Sixteen patients (51.6%) underwent invasive EEG. By the last follow-up (median = 5 years, interquartile range = 3.3-9 years), seizure freedom was achieved in 71% of patients (22/31), including seven of eight MRI-negative patients. Antiseizure medications were reduced in 21 patients, with complete withdrawal in six. Seizure outcome was predicted by a combination of the following descriptors: age at epilepsy onset, epilepsy duration, long-term invasive EEG, and specific MRI and PET findings. SIGNIFICANCE: This study highlights the broad phenotypic spectrum of FCD type 1, which spans far beyond the narrow descriptions of previous studies. The applied multilayered presurgical approach helped localize the epileptogenic zone in many previously nonlesional cases, resulting in improved postsurgical seizure outcomes, which are more favorable than previously reported for FCD type 1 patients.
Keywords: Epilepsy; Magnetic Resonance Imaging; magnetická rezonanční tomografie; epilepsie; Infant; Humans; kojenec; dítě; malformace mozkové kůry; kohortové studie; Drug Resistant Epilepsy; Child; Female; výsledek terapie; lidé; Malformations of Cortical Development, Group I; elektroencefalografie; Malformations of Cortical Development; Cohort Studies; předškolní dítě; Focal Cortical Dysplasia; refrakterní epilepsie; ženské pohlaví; Male; Adolescent; Treatment Outcome; Positron-Emission Tomography; malformace mozkové kůry, skupina I; Electroencephalography; mužské pohlaví; Child, Preschool; fokální kortikální dysplazie; pozitronová emisní tomografie; mladiství